(untitled) (Community Based Medical Journal, 2025)
A cross-sectional, descriptive type study was done in the Department of Anatomy, Mymensingh Medical College, Bangladesh, between October 2008 and March 2009, to determine the position of the anterior commissure in relation to the anterior height of the thyroid cartilage in cadavers and observe gender difference, if any. A total of 29 postmortem human larynges (male 17 and female 12) were collected from dead bodies (aged between 17 to 60 years) from the mortuary of the Department of Forensic Medicine of the same institution. In the present study, the mean value of the ratio of the distances between the superior thyroid notch and anterior commissure and the midline height from thyroid notch to the inferior border of thyroid cartilage was found 0.23 in females and 0.26 in males. No statistical differences were observed between these two groups (p>0.05). It was also found that anterior commissure lies at the junction of upper one fourth and lower three fourth of the anterior height of thyroid cartilage. CBMJ 2025 January: Vol. 14 No. 01 P: 22-27